Symptom profiles in the painDETECT Questionnaire in patients with peripheral neuropathic pain stratified according to sensory loss in quantitative sensory testing. Issue 8 (August 2016) - Vollert, Jan; Kramer, Martin; Barroso, Alejandro; Freynhagen, Rainer; Haanpää, Maija; Hansson, Per; Jensen, Troels S.; Kuehler, Bianca M.; Maier, Christoph; Mainka, Tina; Reimer, Maren; Segerdahl, Märta; et al.
Abstract : Abstract: The painDETECT Questionnaire (PDQ) is commonly used as a screening tool to discriminate between neuropathic pain (NP) and nociceptive pain, based on the self-report of symptoms, including pain qualities, numbness, and pain to touch, cold, or heat. However, there are minimal data about whether the PDQ is differentially sensitive to different sensory phenotypes in NP. The aim of the study was to analyze whether the overall PDQ score or its items reflect phenotypes of sensory loss in NP as determined by quantitative sensory testing. An exploratory analysis in the Innovative Medicines Initiative Europain and Neuropain database was performed. Data records of 336 patients identified with NP were grouped into sensory profiles characterized by (1) no loss of sensation, (2) loss of thermal sensation, (3) loss of mechanical sensation, and (4) loss of thermal and mechanical sensation. painDETECT Questionnaire profiles were analyzed in a 2-factor analysis of variance. Patients with loss of thermal sensation (2 and 4) significantly more often reported pain evoked by light touch, and patients with loss of mechanical sensation (3 and 4) significantly more often reported numbness and significantly less often burning sensations and pain evoked by light touch . Although the PDQ was not designed to assess sensory loss, single items reflect thermal and/or mechanical sensory loss at group level, but because of substantial variability, the PDQ does not allow for individual allocation of patients into sensory profiles. It will be useful to develop screening tools according to the current definition of NP. Abstract : Although not designed for this purpose, painDETECT Questionnaire items exhibit group differences between neuropathic pain patients with or without sensory loss.